Possibilidades de pesquisa no Portal de Periódicos CAPES - Siqueira, Thiago Giordano de Souza (Brasil, 2020)
Presents the possibilities of searching for information by subject, book, based on the CAPES Journal Portal. Demonstrates how to access the Portal remotely using access via the CAFe network. Features tips on Boolean operators. Virtual training on the Portal and the application for use on the mobile phone.